Pharmacological Treatment of Alzheimer’s Disease: Is it Progressing Adequately? - Robles, Alfredo (Bentham Open, 2009)
INTRODUCTION: Between 1993 and 2000 four acetylcholinesterase inhibitors were marketed as a symptomatic treatment for Alzheimer’s disease (AD), as well as memantine in 2003. Current research is focused on finding drugs that favorably modify the course of the disease. However, their entrance into the market does not seem to be imminent. RESEARCH DEVELOPMENT: The aim of AD research is to find substances that inhibit certain elements of the AD pathogenic chain (beta- and gamma-secretase inhibitors, alpha-secretase stimulants, beta-amyloid aggregability reducers or disaggregation and elimination inductors, as well as tau-hyperphosphorylation, glutamate excitotoxicity, oxidative stress and mitochondrial damage reducers, among other action mechanisms). Demonstrating a disease’s retarding effect demands longer trials than those necessary to ascertain symptomatic improvement. Besides, a high number of patients (thousands of them) is necessary, all of which turns out to be difficult and costly. Furthermore, it would be necessary to count on diagnosis and progression markers in the disease’s pre-clinical stage, markers for specific phenotypes, as well as high-selectivity molecules acting only where necessary. In order to compensate these difficulties, drugs acting on several defects of the pathogenic chain or showing both symptomatic and neuroprotective action simultaneously are being researched. CONCLUSIONS: There are multiple molecules used in research to modify AD progression. Although it turns out to be difficult to obtain drugs with sufficient efficacy so that their marketing is approved, if they were achieved they would lead to a reduction of AD prevalence.